Vocabulary practicing from assisting techniques in three dimensional animation with user interaction - Kornprom Pikulkaew (2019)
© 2018 IEEE. For some group of people, learning a new language such as English language can be considered to be a hard and time-consuming task to accomplish. As a result, these group of people can be discouraged and finally stop putting effort into continuity of learning a new language. They may even lack their motivation or their cheerful heart. This research thus aims to propose an efficient approach to cheer up people who want to study a non-native language. The proposed approach, in order to achieve the purpose, is to use game-based and user-interactive interfaces, in other words, to use a serious gaming technology applying to the non-native language learning (or practicing). From the experimental results of our example of a serious game for learning English vocabularies, the game provides highly impact on engaging people to continue practicing for higher lessons, also it helps them get a positive attitude towards the practice and thus have a good progress. Moreover, every user tested on our approach will not learn only how to use appropriate vocabularies, but also prepositions so that they may improve their English grammar further.